Analysis of Geographical Distribution and Patronage of Fast Food in Calabar Urban, Nigeria - Violet Bassey Eneyo; Michael Anake Ushie; Linus Beba Akeh; Rose Ekaete Udonwa; Stella Bassey Esuabana; Delight Omoji Idika; Prince-Charles Omin Itu; Agnes Sylvester Antai (African Journal of Hospitality, Tourism and Leisure, 2022)
The study examined fast food's geographical distribution and patronage in Calabar urban, Nigeria. Data were acquired from both secondary and primary sources. Inferential and descriptive statistical techniques were used to analyse the acquired data for the study. The findings indicated a clustered pattern of forty-seven operating fast-food outlets scattered across the area. The study also observed that large population density, central city business and shopping districts known as the CBD/tourist attractions and security were the main factors of fast food location. Furthermore, the study revealed a substantial negative correlation between patrons' distance from the fast food outfits and their frequency of patronage, meaning that the larger the distance between patrons and fast-food establishments, the lower the degree of patronage. The study further showed that fast food patronage fluctuates substantially depending on the time of day. The study recommended that fast food proprietors and government evaluate the critical factors of the geographical distribution of fast food in the area for the long-term viability of the business.